PENDIDIKAN KOGNITIF BERBASIS KARAKTER - Zulkarnain Zulkarnain (TASÂMUH, 2015)
Character-based cognitive education can be seen as the oldest assessment in educational history. This assessment focuses on measuring of educational evaluation process. Measurement cannot be separated from the meaning of quantity. This quantity will determine amount (magnitude) of objects, persons, and events which are described in units of certain measurement. In educational scope, assessment which has character in cognitive development has been implemented in educational process to see and reveal individual differences and group in skill, interest, attitude, and personality; and very basic education in nation generation life is character education because the existence of human resources quality that have character will determine the progress of nation. Qualified character needs to be formed and guided when it wasearly age because early age forms decision phases for formation of personal character. Therefore, parents’ success in guiding their children in solving personality conflict in early age determines children’s success in social life in their future.